Student Responses to Hydrostatic Pressure Physics Learning Using the Phet Simulation-Based Inquiry Method - Lola Salsabila; Fauzan Sulman; Aminah Zb (JUPE : Jurnal Pendidikan Mandala, 2026)
The purpose of this study was to determine students' responses to learning about hydrostatic pressure using the PhET Simulation-based inquiry method. Simulation-based learning was chosen because the material on hydrostatic pressure is abstract and requires visualization to improve conceptual understanding. Understanding the concept is a process for someone to think in order to be able to understand and understand a concept in learning and also to process a learning material that will be received so that it becomes more (Fitriyani et al., 2023). The research was conducted at MAN 2 Kota Jambi with 15 students from class XI F8 selected using purposive sampling. The research approach used a quantitative approach with a descriptive method. The research instrument was a 1–5 Likert scale questionnaire consisting of 10 statements, covering two main aspects: (1) attitude towards the PhET Simulation media, and (2) general attitude towards learning. Data were collected after students participated in inquiry-based learning that allowed them to explore the variables of depth, density, and gravity through independent simulation.The descriptive analysis results show that the overall average score was 4.12, which falls into the "Good" category. In terms of attitudes toward PhET media, the average score of 4.12 indicates that students felt helped in understanding the concepts and enjoyed the learning process. In terms of general attitudes toward learning, the average score of 4.12 indicates an increase in motivation, speed of understanding, and concept retention. The highest score was on the statement regarding the ease of remembering concepts (Fitriyani et al., 2023)(4.4), while the lowest score came from several individual responses that did not affect the general trend. Overall, PhET Simulation-based inquiry learning received a positive response ( ) from students and was considered effective in improving their understanding of physucs concepts, especially hydrostatic pressure. This learning model is recommended for application tp other physics materials that require interactive visualization.